2010
DOI: 10.1007/s10654-010-9434-8
|View full text |Cite
|
Sign up to set email alerts
|

Can incentives undermine intrinsic motivation to participate in epidemiologic surveys?

Abstract: Response rates to surveys are decreasing. The purpose of this study was to evaluate the use of lottery tickets as incentives in an epidemiologic control group. A self-administered questionnaire was sent to parents in the municipality of Stockholm, Sweden, who were to be used as a control group in a study addressing stress in parents of children with cancer. A stratified random sample of 450 parents were randomized into three incentive groups: (a) no incentive; (b) a promised incentive of one lottery ticket to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Research questions either emerging from the communities or being approved by them lead to facilitation and support regarding recruitment of participants and the collecting of data. The respondent’s engagement is an important factor for higher participation rates but also for better quality of data [8]. Feedback and options to use the results in health enhancing interventions increase willingness to participate in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research questions either emerging from the communities or being approved by them lead to facilitation and support regarding recruitment of participants and the collecting of data. The respondent’s engagement is an important factor for higher participation rates but also for better quality of data [8]. Feedback and options to use the results in health enhancing interventions increase willingness to participate in future research.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge in research today is low response rate [8]. In epidemiological studies, participation is normally lower in groups with less than optimal health outcomes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some studies have reported that incentives may not be beneficial [1,12,28]. Wenemark et al suggests that the positive impact of incentives may be specific to consumer related research.…”
Section: Discussionmentioning
confidence: 99%
“…Wenemark et al suggests that the positive impact of incentives may be specific to consumer related research. It is speculated that incentives may insult or annoy potential respondents when the research is health related; that is, subjects may already feel an obligation towards participating in medical research, and offering incentives may induce suspicions of ulterior motives [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Paper questionnaires are widely used to collect data for medical and health services researches [1], [2], [3], [4], [5] and [6]. However, much variation in response rates has been observed.…”
Section: Introductionmentioning
confidence: 99%